Exploring the depths of IgG4: insights into autoimmunity and novel treatments - Ünlü, Selen; Sánchez Navarro, Blanca G.; Cakan, Elif; Berchtold, Daniel; Meleka Hanna, Rafael; Vural, Secil; Vural, Atay; Meisel, Andreas; Fichtner, Miriam L. (Frontiers in Immunology, 2024)
IgG4 subclass antibodies represent the rarest subclass of IgG antibodies, comprising only 3-5% of antibodies circulating in the bloodstream. These antibodies possess unique structural features, notably their ability to undergo a process known as fragment-antigen binding (Fab)-arm exchange, wherein they exchange half-molecules with other IgG4 antibodies. Functionally, IgG4 antibodies primarily block and exert immunomodulatory effects, particularly in the context of IgE isotype-mediated hypersensitivity reactions. In the context of disease, IgG4 antibodies are prominently observed in various autoimmune diseases combined under the term IgG4 autoimmune diseases (IgG4-AID). These diseases include myasthenia gravis (MG) with autoantibodies against muscle-specific tyrosine kinase (MuSK), nodo-paranodopathies with autoantibodies against paranodal and nodal proteins, pemphigus vulgaris and foliaceus with antibodies against desmoglein and encephalitis with antibodies against LGI1/CASPR2. Additionally, IgG4 antibodies are a prominent feature in the rare entity of IgG4 related disease (IgG4-RD). Intriguingly, both IgG4-AID and IgG4-RD demonstrate a remarkable responsiveness to anti-CD20-mediated B cell depletion therapy (BCDT), suggesting shared underlying immunopathologies. This review aims to provide a comprehensive exploration of B cells, antibody subclasses, and their general properties before examining the distinctive characteristics of IgG4 subclass antibodies in the context of health, IgG4-AID and IgG4-RD. Furthermore, we will examine potential therapeutic strategies for these conditions, with a special focus on leveraging insights gained from anti-CD20-mediated BCDT. Through this analysis, we aim to enhance our understanding of the pathogenesis of IgG4-mediated diseases and identify promising possibilities for targeted therapeutic intervention.